PENANAMAN NILAI-NILAI AGAMA ISLAM MELALUI MEDIA VIDEO PEMBELAJARAN PADA ANAK USIA DINI DI TK AL-MUHAJIRIN LAMPUNG UTARA - Rita Muryati; Oppi Sari Wulan; siti Patimah; M. Makhrus Ali; A. Latief Arung Arafah (TADBIRUNA: Jurnal Manajemen Pendidikan Islam, 2022)
The instillation of Islamic religious values in early childhood is a fundamental step in character building. Video media as an interactive learning tool offers an innovative and effective approach in delivering these values. This article discusses the use of video media in instilling Islamic religious values in early childhood at Al Muhajirin Kindergarten in Lampung Utara, as well as the positive impacts produced. Using a qualitative approach, this study analyzes the effectiveness of video media in enhancing understanding and application of Islamic values among children at Al Muhajirin Kindergarten in Lampung Utara. The study results show that videos can increase children's interest and engagement in learning. Videos with interesting and relevant content can influence children's attitudes towards positive values such as honesty and compassion. However, the involvement of parents and teachers remains important in guiding and ensuring appropriate content. This study provides new insights into the use of technology in religious education and highlights the importance of collaboration between technology and educators to achieve optimal learning outcomes